Comparison of Carbol Fuchsin Concentration on the Results of Acid-Fast Bacteria Staining (AFB) - Al Adawiah, Putri Rabiah; Basarang, Mujahidah; Rantung, Juneke Gabriella (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: Infections caused by the bacterium Mycobacterium tuberculosis are known as tuberculosis. (TB). The treatment process takes a long time because this bacillus bacteria is very strong. Compared to other parts of the human body, this bacteria more frequently attacks the lungs. Patients who test positive for acid-fast bacilli (AFB) are the cause of pulmonary tuberculosis (TB). The aim of this research is to determine how the concentration of Carbol Fuchsin differs in the results of Acid-Fast staining. (BTA). Method: This research was conducted in a laboratory and used purposive sampling techniques with the Ziehl-Neelsen staining method, resulting in 5 positive acid-fast bacilli (AFB) samples. Result: The results of this study indicate that the best concentration is 1.5% carbol fuchsin, so it can be concluded that the optimal staining concentration is 1.5% carbol fuchsin. Conclusion: Based on the research conducted, it was concluded that the higher the concentration of carbol fuchsin, the stronger it binds to the cell walls that have a lipid layer, thus being able to bind the red colour.